The Effect of Meditation on Improving Emotion Regulation in Indonesian Pencak Silat Kelatnas Members Perisai Diri, Sidoarjo Junior High School: Pengaruh Meditasi dalam Meningkatkan Regulasi Emosi pada Anggota Pencak Silat Kelatnas Indonesia Perisai Diri Unit Sekolah Menengah Pertama Sidoarjo - Putra, Yunus Brahmana; Dewanti, Ririn (Universitas Muhammadiyah Sidoarjo, 2021)
This research is motivated by the phenomenon of members of the Indonesian National Martial Arts Academy Perisai Diri unit SMP X Sidoarjo who experience problems with their emotional regulation abilities. One way that can be used to improve the ability to regulate emotions is to practice meditation. The purpose of this study was to determine the effect of meditation in increasing the ability to regulate emotions in members of the Indonesian National Martial Arts Academy Perisai Diri unit at SMP X Sidoarjo. This study used a pre-experimental method with a one-group pretest-posttest research design. The meditation used is meditation from the Perisai Diri martial arts school, consisting of mindfulness and loving kindness techniques. The subjects in this study consisted of 13 pencak silat members who were given a pretest to measure their initial emotional regulation ability, then meditation treatment was given to the subject, after that a posttest was given after meditation treatment was given to the subject to measure emotion regulation ability. The results of hypothesis testing using the calculation of the Paired Sample t-test showed a significance value of 0.00 (p <0.05), which means that the hypothesis is accepted. Thus, it can be concluded that meditation has an effect on increasing emotional regulation in members of the Indonesian National Martial Arts Academy, the Perisai Diri unit, SMP X Sidoarjo.